Natural resources assessment, application, and projects for the agricultural sector of Antigua and Barbuda (OAS WashingtonUS, 1992)
Summarizes the main technical studies of the Natural Resources Assessment for Agricultural Development (NRAD) Project begun in 1984 under the National Technical Cooperation Agreement between the Antigua and Barbuda Government and the OAS. Aims to improve Government's facility to plan, prepare and effect future agricultural development.
Bibliography: p.131-132